Treatment of intraoral ranulas with a two-incision fistula technique: the management of recurrence. Issue 2 (February 2018) - Zhao, Qingtong; Li, Mengyu; Lai, Renfa; Wang, Shaoyi
Abstract: The two-incision fistula technique for the treatment of oral ranulas has recently been introduced to clinical practice. We reviewed 52 patients who had recurrences after this treatment, and explored the possible causes and underlying mechanisms. A total of 13/53 ranulas had recurred, so we repeated the operation, and one patient had the ranula and the sublingual gland resected. We found that the thin mucous membrane cracked at the double incisions, which led to the formation of a fistula and promoted the drainage of cystic fluid. The results indicated that the recurrence of ranulas after the two-incision fistula technique can be reduced further. To avoid recurrence, the technique should be adjusted slightly, depending on the type of ranula present.